Perspectives on push–pull chromophores derived from click-type [2 + 2] cycloaddition–retroelectrocyclization reactions of electron-rich alkynes and electron-deficient alkenes - Yamada, Michio (Beilstein Journal of Organic Chemistry, 2024)
Various push–pull chromophores can be synthesized in a single and atom-economical step through [2 + 2] cycloaddition–retroelectrocyclization (CA–RE) reactions involving diverse electron-rich alkynes and electron-deficient alkenes. In this review, a comprehensive investigation of the recent and noteworthy advancements in the research on push–pull chromophores prepared via the [2 + 2] CA–RE reaction is conducted. In particular, an overview of the physicochemical properties of the family of these compounds that have been investigated is provided to clarify their potential for future applications.
Keywords: click chemistry; donor–acceptor conjugate; intramolecular charge transfer; photoluminescence; photoinduced electron transfer